2013
DOI: 10.1371/journal.pone.0084776
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus Is Associated with Hepatocellular Carcinoma: A Retrospective Case-Control Study in Hepatitis Endemic Area

Abstract: BackgroundA number of case-control patient studies have been conducted to investigate the association between diabetes mellitus (DM) and hepatocellular carcinoma (HCC). Despite some controversial reports, it has been suggested that DM is associated with HCC. The previous studies on this subject vary in the selection of populations, sample sizes, methodology, and analysis results. Therefore, it is necessary to further delineate the involvement of DM, together with other related risk factors, in HCC with large s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
(40 reference statements)
0
22
0
2
Order By: Relevance
“…Recent studies have shown that DM may be a potential risk factor for HCC[5,7,8], and this hypothesis has been supported by several case control[9-12] and cohort studies[13-17]. Additionally, increased HCC prevalence in the diabetic population has been reported, possibly due to steatohepatitis[7,9].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Recent studies have shown that DM may be a potential risk factor for HCC[5,7,8], and this hypothesis has been supported by several case control[9-12] and cohort studies[13-17]. Additionally, increased HCC prevalence in the diabetic population has been reported, possibly due to steatohepatitis[7,9].…”
Section: Introductionmentioning
confidence: 89%
“…The incidence of hepatocellular carcinoma (HCC) in China is dramatically increased by HBV infection, which is the main cause of HCC[3,4]. Over 70% of cases of HCC in China have been associated with HBV infection[5]. …”
Section: Introductionmentioning
confidence: 99%
“…Viral infection in HCC cases was commonly observed to be copresent with other etiologic factors of this malignancy (6)(7)(8). It has been reported that in areas with a high prevalence of hepatitis viral infections, 8.4% to 24.1% of HBV/HCV-related HCC cases presented with type 2 diabetes (7, 9-12), 19.6% to 41.7% with hypertension (11,12), 5.4% to 23.4% with alcohol abuse (13), and 28.3% to 33.0% with smoking habits (4,13). Previous studies have demonstrated synergistic effects between HCV infections and alcohol consumption (2), obesity and diabetes (7,14).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, a number of studies have shown that HCV promotes IR through viral‐associated mechanisms as well as activation of various inflammatory processes . The evidence for this association comes from a number of different sources including studies from tertiary care centres, population‐based studies, basic science research and therapeutic clinical trials of HCV . The association is strongest for HCV genotype 3 but remains important for all HCV genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, a number of reports from both cohort and population‐based studies have suggested an association between hepatitis C virus (HCV) infection and insulin resistance (IR) and type 2 diabetes (DM) . HCV‐induced diabetes mellitus is currently believed to be a result of insulin resistance in both hepatic and peripheral tissue.…”
Section: Introductionmentioning
confidence: 99%